Infinite volume and atoms at the bottom of the spectrum - Edwards, Sam; Fraczyk, Mikolaj; Lee, Minju; Oh, Hee (Comptes Rendus. Mathématique)
Let $G$ be a higher rank simple real algebraic group, or more generally, any semisimple real algebraic group with no rank one factors and $X$ the associated Riemannian symmetric space. For any Zariski dense discrete subgroup $Γ